Incidence and Risk Factors of Gastrointestinal Bleeding in ICU Patients: A Four-Year Cohort Study: Insidensi dan Faktor Risiko Pendarahan Gastrointestinal pada Pasien ICU: Studi Kohort Selama Empat Tahun - Ali Sadie Alhashemi; Hasanain Abdul-Muhsin; Ahmed Amer Abdul Hussein (Academia Open, 2023)
This study aims to investigate the frequency and potential causes of gastrointestinal bleeding (GIB) in Intensive Care Units (ICUs) while focusing on the associated risk factors. Conducted as a cohort study in critical care centers at Ghazi AL Hariri Teaching Hospital for Special Surgeries and Burn Specialty Teaching Hospital at Medical City Complex in Baghdad, Iraq, spanning from 2018 to 2022, the research analyzed patients with clinically significant GIB upon admission to the ICU using univariate and multivariate intervention analyses. The key findings revealed that 1.3% of ICU cases developed GIB without prior symptoms, with risk factors including prolonged ICU stays, elevated creatinine levels, elevated bilirubin, and heightened Aspartate Aminotransferase activity. Alarmingly, 47% of GIB-diagnosed ICU patients faced mortality during their hospitalization, significantly higher than non-GIB patients (30%). This study underscores the importance of vigilance and early detection for high-risk patients, given the significant morbidity and mortality associated with GIB in the ICU population, despite its declining incidence. Highlights : This cohort study investigates the frequency and risk factors associated with gastrointestinal bleeding (GIB) in ICU patients. Prolonged ICU stays, elevated creatinine and bilirubin levels, and increased Aspartate Aminotransferase activity are identified as risk factors for GIB development. Alarmingly, GIB-diagnosed ICU patients have a significantly higher mortality rate (47%) compared to non-GIB patients (30%), highlighting the critical importance of early detection and vigilance in managing this condition. Keywords: Gastrointestinal Bleeding, Intensive Care Units, Risk Factors, Mortality, Cohort Study